PENGEMBANGAN WILAYAH BERBASIS POTENSI SEKTOR UNGGGULAN DI KABUPATEN GOWA - Edo Pramana Putra; Kasmiati Kasmiati (Mega Aktiva, 2018)
Regional development policy that based on leading sector potentials had not been adapted to the carryng capacity of the area in Gowa. moreover, the data distribution of regional  commodity-based geographic information system (GIS) was unavailable. Therefore , this study aimed to determine the commodity in Gowa, and map distribution of commodity in each district in Gowat that could be the basis for regional development policies in the region. The analytical tool used was the Klassen Typology which classified   the economic sector growth patterns in Gowa and Location Quation (LQ) analysis to determine the leading sectors. Then, the descriptive analysis and GIS were carried and see distribution of sub-sectors that aproppriate in each region. Klassen typology analysis results show, the agricultural sector is an advanced sector but deprssed, contribute the economy of Gowa in very large scale of 44%  (from 2009 to 2013). However, based on the results of the analysis LQ not only agricutural sector come out leading sectors including finance, real estate and business services sector. On the frame of sustainability development in Gowa, the agricutural is still eligible as leading sector , sice the sector is still dominated the source of income.